2012
DOI: 10.1155/2012/265249
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Studies of L-Histidine Complexes of Pb(II), Cd(II), and Hg(II) in DMSO-Water Mixtures

Abstract: , and ML. The appropriateness of experimental conditions is verified by introducing errors intentionally in the concentrations of ingredients. The models containing different numbers of species were refined by using the computer program MINIQUAD75. The best-fit chemical models were arrived at based on statistical parameters. The trend in variation of stability constants of the complexes with dielectric constant of the medium is attributed to the electrostatic and nonelectrostatic forces. The species distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Despite ApT solution being considered able to form a stable solution in DMSO, it is also considered a competitive solvent because it also interacts with the cations, due to the intermolecular interactions present in the solution and lone pairs of electrons available in its molecule. Several studies have reported DMSO‐metal ions interaction .…”
Section: Resultsmentioning
confidence: 99%
“…Despite ApT solution being considered able to form a stable solution in DMSO, it is also considered a competitive solvent because it also interacts with the cations, due to the intermolecular interactions present in the solution and lone pairs of electrons available in its molecule. Several studies have reported DMSO‐metal ions interaction .…”
Section: Resultsmentioning
confidence: 99%
“…Organic molecules with side chains other than amine groups, as oxygen motifs, may represent possible candidates for inducing charge redistribution and produce 2D local magnetism in RP hybrid perovskites. Some organic active sites are potential binding centers, and among the possibilities, the l -histidine molecule is one of the strongest metal coordinating ligands in the amino acid family . Histidine molecules have three potential interacting sites, carboxylate oxygen, imidazole imido nitrogen, and amino nitrogen .…”
mentioning
confidence: 99%
“…It is known as one of the strongest metal coordinating ligands among AAs. 85,118 Although using His to synthesize CsPbBr 3 had minimal impact on their optical properties, 62 it was successfully used to grow 2D layered structures based on MAPbI 3 Ruddlesden-Popper (RP) perovskites with n = 2 and 3 (Fig. 3c).…”
Section: Hpmentioning
confidence: 99%